Management of gunshot-induced fractures in the maxillofacial region: case report and literature review - Godoy-Tercero, Ana Sofía (2026)
The management of fractures in the maxillofacial region caused by firearms represents a challenge that requires immediate multidisciplinary intervention. Treatment is conditioned by the severity of the injury and the structures involved. In this study, three cases of patients admitted to the maxillofacial surgery service due to ballistic trauma with extensive soft-tissue injuries and hard-tissue damage are described. All patients showed favorable clinical evolution following treatment. Additionally, a literature review was conducted to design a management algorithm for fractures caused by firearms based on established protocols.